2016
DOI: 10.4238/gmr.15038363
|View full text |Cite
|
Sign up to set email alerts
|

Association between the interleukin 4 gene -590C>T promoter polymorphism and asthma in Xinjiang Uighur children

Abstract: ABSTRACT. We investigated the association between the interleukin 4 gene (IL-4) -590C>T polymorphism and forced expiratory volume in one second (FEV 1 ) values, immunoglobulin E (IgE) levels, and susceptibility to asthma in Uighur children. IL-4 -590C>T frequencies were analyzed in 38 bronchial asthmatic patients and 35 non-asthmatic controls. Polymerase chain reaction and direct sequencing were applied to determine the residue at position -590 of IL-4. Total serum IgE levels were detected by enzyme-linked imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to the criteria, a total of seven articles were selected, 15 , 16 , 17 , 18 , 19 , 20 , 21 including two in Western countries and five in Asia, with a total of 860 patients in the asthma group and 810 patients in the control group. Details of the filter process were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the criteria, a total of seven articles were selected, 15 , 16 , 17 , 18 , 19 , 20 , 21 including two in Western countries and five in Asia, with a total of 860 patients in the asthma group and 810 patients in the control group. Details of the filter process were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of seven articles 15 , 16 , 17 , 18 , 19 , 20 , 21 were included in the study, of which five were from Asian studies and two were from European and American studies. The results showed a correlation between the IL-4-C590T gene polymorphism and childhood asthma susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…This result was further confirmed at allelic level, where the mutant allele (T) was more frequent among asthma patients than controls with significant difference. Significant association of this SNP with asthma was recorded worldwide such as in Japan (7) , Taiwan (8) , Algeria (9) , Germany (10) , west Siberia (2) , Macedonia (11) , China (12) and Iran (13) . However non-significant association was also previously reported in United Kingdom (14) , China (15) and Brazil (16) .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, EOS activation, proliferation, release a variety of pro-inflammatory mediators, cause chronic allergic reactions, and destroy their own tissues and functions. A number of studies have suggested that IL-4 gene polymorphism is closely related to bronchial asthma and respiratory hyperresponsiveness (3), but there have been some differences in the conclusions of recent studies, which have also involved small sample sizes (4). A number of studies have suggested that high expression of the IL-4-590C/T gene may be an important cause of the inducement of bronchial asthma (5,6).…”
Section: Introductionmentioning
confidence: 99%